Population distribution by selected road network elements - comparison of centroids, geocoded addresses, built-up areas and total areas on the example of Slovak communes - Bačík Vladimír; Klobučník Michal (Bulletin of Geography. Socio-Economic Series)
Two research objectives can be identified in the presented paper. The first one was the development of a point layer, which would abstract from the position of a central point depending on the shape of the territory of the respective spatial unit (commune), and would express the position of a commune as regards the location of the point in the area of the commune built-up area. For such purpose, a geocoding algorithm from Google was used, for which it was possible to prepare a final dot map layer without any terrain layout, as the geocoding algorithm processes only simple text addresses of the relevant spatial units. Such an obtained dot layer was compared with the layer of centroids and the achieved differences were visualised. Another objective was to compare different methods of population distribution interpretation from the selected road network elements at the commune level. Point layers in the form of centroids and geocodes were compared with the spatial population distribution on the basis of the total area and built-up area of a commune.